Decadal review: How gender and race of geoscientists are portrayed in physical geology textbooks. Issue 1 (2nd January 2020) - Bush, Paige; Mattox, Stephen
Abstract: Attracting more students to the geosciences is imperative. We have an excellent opportunity to model an inclusive community, with hundreds of thousands of students passing through introductory college courses each year. A previous study documented gender and racial bias in physical geology textbooks. Six texts were reexamined to determine any progress. Individuals or groups engaged in scientific activities were considered geologists. Geologists were shown in 567 (8.6%) of the 6593 photos. Of the 499 identifiable geologists in the photos, 346 are male (69.3%), 153 are female (30.7%). Out of 346 males, 307 are white (88.7%), 20 are racially diverse (5.8%), and 19 are unknown (5.5%). Out of 153 females, 137 are white (89.6%), 10 are racially diverse (6.5%), and 6 are unknown (3.9%). The more recent editions of the textbooks showed 2.8 times more photos of geologists. Physical geology books portrayed males as 2.3 times more likely to be geologists than females. This ratio significantly exceeds the near equal proportions of men and women entering the geosciences. The books implied that white geologists are nearly 15 times more abundant in the workforce compared to their nonwhite peers. This ratio differs significantly from the data for recent graduates and the general U.S. population (about 3:1 for both data sets). The number of identifiable minority geologists increased to 30 from the original 8. These numbers remain discouragingly low, and some double minorities—such as African-American females and Asian females—are rare (10 of 6593 photos) or absent (female Latinx, 0 of 6593 photos). Solutions are available in our community, such as constructing and sharing a database of photos of diverse geoscientists, asking illustrators to add diverse scientists into their figures, and mining public and professional organizations' stocks of photographs.